2021
DOI: 10.1007/s00259-021-05472-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased uptake of 68Ga-DOTA-FAPI-04 in bones and joints: metastases and beyond

Abstract: Purpose: To describe the uptake of 68 Gallium-labelled broblast activation protein inhibitor ( 68 Ga-FAPI) in bones and joints for better understanding of the role of 68 Ga-FAPI PET in benign and malignant bone lesions and joint diseases.Methods: All 129 68 Ga-FAPI PET/MR or PET/CT scans from June 1, 2020 to February 20, 2021 performed at our PET centre were retrospectively reviewed. Foci of elevated 68 Ga-FAPI uptake in bones and joints were identi ed. All lesions were divided into malignant and benign diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…This is caused by fibrotic activity in these conditions [ 26 ]. Thus, more researches focused on non-tumor–specific uptake of FAPI are still needed [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by fibrotic activity in these conditions [ 26 ]. Thus, more researches focused on non-tumor–specific uptake of FAPI are still needed [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their selective and strong binding to FAP, a multitude of radiolabeled FAP inhibitors (FAPI) have been generated and are now widely used in experimental tumour diagnosis (reviewed in [10,14]). Several FAPI tracers recently entered the clinical phase for pan-tumour imaging, diagnosis, and staging examinations (Table S1) [121]. To turn the FAPI radiopharmaceuticals into theranostics, the linker region was modified to obtain improved tumour retention and to allow the use of radionuclides suited for therapy [122].…”
Section: Fapmentioning
confidence: 99%
“…In this scenario, a recent article compared the radiolabeled FAPI uptake in bones and joints between malign and benign lesions (such as periodontitis, osteofibrous dysplasia, degenerative bone disease, arthritis and trauma related lesions) [ 21 ]. The authors reported that, even if overlap occurred in some cases, maximum standardized uptake value (SUV max ) of bone metastases was significantly higher compared to benign lesions, even if no significant differences in terms of uptake between such benign lesions was reported, with the exception of periodontitis.…”
mentioning
confidence: 99%